An Analysis of Competition-based Television Reality Shows in Nigeria - Samuel Olaniran (Covenant Journal of Communication, 2021)
Television reality shows have amassed incredible popularity with high-profile viewership and become a topic of wide-ranging criticisms in Nigeria. This study analyzes the country's entertainment scene changes through reality show programming. In the cards are factors influencing gratification, viewing habits, and attraction to reality shows, using an online survey of 464 respondents. The work anchors on the sensitivity theory of motivation and offers a unique analysis of the primary motivations of respondents for their preferred reality shows and their attraction to them. Findings show that the audience perceived the 'real' in reality genre as partially scripted and content less informative. The respondents also showed higher attraction to singing competition reality shows. Producers should use social media platforms for feedback to enhance reality show programming. They can engage more non-actors and actresses to escalate the ‘reality’ concept and improve the integrity of the shows.